2019
DOI: 10.2147/ott.s208318
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC00958-MYC positive feedback loop modulates resistance of head and neck squamous cell carcinoma cells to chemo- and radiotherapy in vitro</p>

Abstract: Background Aberrant long non-coding RNA (lncRNA) expression contributes cancer development and resistance to therapy. This study first assessed expression of lncRNA LINC00958 in a variety of human cancers using GEPIA database data and then associated it with prognosis of head and neck squamous cell carcinoma (HNSCC) and investigated LINC00958 interaction with c-Myc and the c-Myc-related gene interplay in HNSCC cells. Materials and methods A cohort of 48 HNSCC vs normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
4
17
0
Order By: Relevance
“…The inhibitory effects of LINC00958 knockdown on LAD cells proliferation, migration and invasion revealed the oncogenic properties of LINC00958 in LAD. This observation showed similarity to the reports of enriched present research on the oncogenic nature of LINC00958 in pancreatic cancer, gastric cancer (GC) and cervical cancer [26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…The inhibitory effects of LINC00958 knockdown on LAD cells proliferation, migration and invasion revealed the oncogenic properties of LINC00958 in LAD. This observation showed similarity to the reports of enriched present research on the oncogenic nature of LINC00958 in pancreatic cancer, gastric cancer (GC) and cervical cancer [26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…[11][12][13] Moreover, it has been found that the expressions of lncRNAs are abnormal during radiotherapy, suggesting that lncRNAs play important roles in the regulation of radioresistance. [14][15][16] In the present study, we found that the expression of LINC01224 increased in irradiation-resistant H1975/IR cells compared with irradiation-sensitive H1975 cells. LINC01224 was transcribed from the enhancer region of ZNF91 and regulated the transcription of ZNF91 by mediating chromatin looping between the ZNF91 enhancer and promoter.…”
Section: Introductionsupporting
confidence: 60%
“…Moreover, they also explore dysregulated ncRNAs expression through comparing radiotherapy-resistant, radiotherapy-sensitive, and normal cancer tissues or cells, so as to discover key ncRNAs that could regulate radiotherapy sensitivity. We summarized the differently expressed ncRNAs in radiotherapy-resistant, radiotherapy-sensitive, and normal cancer tissues or cells as shown in Table 1 ( Qu et al, 2012 , 2015a , b ; Li et al, 2013 ; Li B. Y. et al, 2017 ; Li L. N. et al, 2017 ; Li et al, 2020 ; Shiiba et al, 2013 ; Zhang et al, 2013 ; Wang et al, 2014 , 2016 , Wang Z. et al, 2019 ; de Jong et al, 2015 ; Lin et al, 2015 ; Maia et al, 2015 ; Suh et al, 2015 ; Sun et al, 2015 ; Xu et al, 2015 ; Zhao et al, 2015 ; Huang et al, 2016 , 2018 , 2019 ; Kang et al, 2016 ; Weng et al, 2016 ; Wu et al, 2016 , 2018 ; Gao et al, 2017a , b ; Han et al, 2017 ; Hu et al, 2017 ; Chen H. et al, 2018 ; Chen et al, 2019 ; Feng et al, 2018 ; He et al, 2018 ; Yang et al, 2018 ; Kong et al, 2019 ; Tian et al, 2019 ; Vahabi et al, 2019 ; Yi et al, 2019 ; Gou et al, 2020 ; Kangboonruang et al, 2020 ; Shuai and Huang, 2020 ).…”
Section: Ionizing Radiation Modulates Ncrna Expression Profilingmentioning
confidence: 99%